Acceptance of electronic payment systems: A critical review forward a parsimonious model including vertical and horizontal cultural orientations - Hassana Hilale; Abdellatif Chakor (Telematics and Informatics Reports, 2024)
ABSTRACT: The opportunities for prosperity and sustainable development offered by Electronic Payment Systems (EPS) are of great interest to both authorities and various stakeholders, especially in developing countries. Needless to say, UTAUT2 explains only 40 % of the actual use's variance. This model lacks certain salient constructs that have proven to be relevant. Based on 41 reviewed articles, this current paper aims to provide an innovative model built on robust theoretical foundations, including two new concepts Contextual Acquaintance that encompasses experience, familiarity, and situational normality, and Overall Reliability which gathers consistency of the technology itself and stakeholders’ reliability. This led us to uncover new endogenous mechanisms without burdening the model with multiple variables. Furthermore, this model incorporates for the first time horizontal and vertical dimensions of collectivism and individualism in the context of EPS adoption, providing a more profound understanding of behaviors in multicultural societies. Finally, this paper provides a research framework for scholars to reduce the redundancies observed in this context.